EFFECT OF BREWING TEMPERATURE AND TIME ON VITAMIN C CONTENT AND ANTIOXIDANT ACTIVITY OF EDIBLE FLOWER INFUSES - Pulung Nugroho; Karina Bianca Lewerissa; Francies Seva Gentaarinda (Department of Food Science and Biotechnology, Faculty of Agriculture Technology, Universitas Brawijaya, 2023)
Dried chrysanthemum, jasmine and butterfly pea are raw materials for dip infused with antioxidant and vitamin C content. This study aimed to determine the effect of temperature and infusion time on vitamin C content and antioxidant activity. A two-factorial design was used with the first factor being the infusion temperature of 30, 50 and 70 °C. The second factor was infusion time of 1, 3 and 5 minute. Vitamin C content was determined by UV spectrophotometric method (Thermo Scientific Genesys 10 S UV), antioxidant activity by DPPH method, and moisture content by moisture analyzer. The optimum results of vitamin C content of dry samples at 30 °C brewing temperature for 3 minutes and 70 °C brewing temperature for 5 minutes was 0.29%. The vitamin C content of the wet flower control at 70 °C for 5 minutes was 0.53%. The optimum antioxidant activity of the dry sample at 50 °C brewing temperature for 3 minutes was 34.61% and that of the fresh flower control at 70 °C brewing temperature for 5 minutes was 94.14%. The moisture content of dried Chrysanthemum was 7.30%, dried Jasmine was 6.25% and dried butterfly pea was 7.24%.